PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA DENGAN KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN - Anggraini, Shinta (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This Research studies the influence of budgeting participation to the managerial performance with the organization commitment and leadership style as the moderating variables. The purpose of the research is to examine the influence of budgeting participation to the managerial performance at Department of Revenue and Financial Management of Surabaya. This Research is meant to find out whether the organization commitment and leadership style moderates of budgeting participation to the managerial performance. This Research is conducted by using questionnaires survey method wich is distributed to 30 respondents. The result of the research shows that the first hypothesis wich states that budgeting participation has an influence to the managerial performance shows that the significant level is 0.003 is smaller than Î±=0.05 which indicates that H1 is accepted which means that the budgeting participation has an influence to the managerial performance. The second hypothesis shows that the significant level is 0.417 which is bigger than Î±=0.05 which indicates that H2 is insignificant. It means that the organization commitment does not moderate the budgeting participation to the managerial performance, and the third hypothesis test (H3) shows that the significant level of 0.004 which is smaller than Î±=0.005. It means that the leadership style moderates the budgeting participation to the managerial performance. Keywords: Budgeting Paticipation, Managerial Performance, Organization Commitment, Leadership Style.